Spatial compression: analysis and approaches to assessment (by the example of the republic of Bashkortostan) - E. R. Mamleeva; M. Yu. Sazykina; N. V. Trofimova (Вестник Северо-Кавказского федерального университета, 2023)
To implement an effective regional policy in the development of the constituent entities of the Russian Federation, a comprehensive assessment of ongoing processes in the economic and social spheres is necessary, which determines the relevance of the topic of this article. The aim of the study is to study the processes of spatial compression of the municipal districts of the Republic of Bashkortostan in 2016–2020. The authors present a review of foreign and Russian studies on the process of spatial compression due to economic and demographic reasons. It is noted that despite the increase in the number of publications on this topic, the research topic remains poorly studied. The work provides an assessment of the degree of spatial compression of the municipal districts of the Republic of Bashkortostan in 2016–2020 based on the analysis of socio-economic processes, generalization and systematization of facts. The indicators characterizing the processes of spatial compression of territories are analyzed. The study specifies municipal districts, in which the average annual rate of reduction of the resident population is more than two percent per year in the study period, which makes it possible to classify these municipalities as shrinking ones. Further interregional research is needed on this topic in order to develop new approaches and practical tools for managing shrinking territories.